Students’ Prefrence Analysis In Using Literary Theories: Undergraduate Thesis - Yulia Sofiani Zaimar; Leni Tiwiyanti; Yosi M Passandaran (Master Program of Sociology, Universitas Malikussaleh,, 2022)
AbstractIn this research, the researchers would like to research, by taking our students, who are writing their thesis as the data objet. Previously, these students took literature classes at Indraprasta PGRI University, in the seventh semester. The idea to conduct this research departs from the problem, that many of these students, who chose theories that were not appropriate, or they only use intrinsic theory (main character) and morals. In addition, many of them did not understand that literary works have strong ties to linguistics. The qualitative research method is used to describe the data from a survey to English Education study Program Indraprasta PGRI University. The result showed: (1) students did not understand language theory, especially literary theory, (2) the lack of knowledge of students about texts, especially literary texts, (3) active teaching and learning process was very helpful for students in absorbing lecture material, and it was not only one party who was active, (4) their friends were also a very influential factor for students, in determining what type of research will be used in the thesis, and (5) the lack of students' ability to analyze texts is what affects their interest in choosing what type of research to use in the process of optimally drafting a thesis for the English Education Study Program students. Keywords: text, context student’s preference, literary approach, type of literary